2020
DOI: 10.14499/indonesianjpharm31iss1pp11
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Analogs Induce Apoptosis and G2/M Arrest In 4T1 Murine Triple-Negative Breast Cancer Cells

Abstract: Chemotherapy is the first-line treatment for triple-negative breast cancer (TNBC), yet toxicity and resistance effects have been the current problems. Curcumin,a natural compound, has been reported to exert anti-proliferative effects on various cancer cells, including breast carcinoma cells. However, the β-diketone moiety influences the stability of curcumin. Curcumin analogs, pentagamavunon-0 (PGV-0), and pentagamavunon-1 (PGV-1) were synthesized to improve the stability and activity of curcumin by modified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The MTT assay method refers to [26] . Colorectal sulfate indicating the total organic compound contained, Dragendorff's reagent indicating tertiary amine moiety, and ninhydrin indicating primary and secondary amines.…”
Section: Mtt Assaymentioning
confidence: 99%
“…The MTT assay method refers to [26] . Colorectal sulfate indicating the total organic compound contained, Dragendorff's reagent indicating tertiary amine moiety, and ninhydrin indicating primary and secondary amines.…”
Section: Mtt Assaymentioning
confidence: 99%
“…The various pharmacological activities of pentagamavunon-0 (PGV-0), an analog of curcumin, have been described in several studies [14][15][16][17][18][19], including its role as an antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that revitalizing adult hippocampal neurogenesis holds enormous potential as an effective therapeutic target for AD. The various pharmacological activities of pentagamavunon-0 (PGV-0), an analog of curcumin, have been described in several studies [14–19], including its role as an antioxidant. Its chemical structure includes phenolic hydroxy and methoxy groups in the ortho position of both aromatic rings, significantly contributing to its potent antioxidant properties and free radical scavenging abilities [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As endogenous antioxidants such as superoxide dismutase (SOD), glutathione peroxidase (GSH), and catalase (Murray, 2003) are produced by our body, exogenous antioxidants come from intakes such as fruits, vegetables, food supplement, herbs, spices, and drugs. The nature provides wide arrays of good external antioxidants with important substances such as vitamin E, vitamin C, and flavonoids are some of the examples (Nimse and Pal, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin analogs are the result of curcumin structure modification. Many of them have been studied for their biological activities (Tomeh et al, 2019;Allegra et al, 2016;Murwanti et al, 2020), including as antioxidant (Simon et al, 2018). Some studies have reported the discovery of compounds in this type, such as Pentagamavunon-0 (PGV-0, Pentagamavunon-5 (PGV-5), Heksagamavunon-5 (HGV-5) (Figure 1) (Reksohadiprodjo et al, 2004) (Yuwono & Oetari, 2004, Tetrahydropentagamavunon-0 (THPGV-0) (Ritmaleni & Simbara, 2010), Tetrahydropentagamavunon-1 (THPGV-1) (Ikawati et al, 2018), and Tetrahydropentagamavunon-5 (THPGV-5).…”
Section: Introductionmentioning
confidence: 99%